Microfluidic chip with multiple functions for sensing - Erh, Gavin Choon Hean (2018)
Microfluidics are widely used in many applications from cell sorting, cell lysis or even molecular detection purposes. In this study, polymethyl(methacrylate) (PMMA) is the material used for the fabrication of the microfluidic chip. The design of the microfluidic chip involves integrating the mixing of the gold nanoparticles with aqueous sodium chloride and the separation of the aggregated gold nanoparticles using microchannels. The design of the chip is replicated from the nickel mold onto the PMMA sample via thermal imprinting process followed by thermal embossing process to create a fully functioning chip. After multiple failed attempts in creating a successful sample, the final few samples were relatively acceptable. Fabricated microfluidic chip was tested for its mixing and size separation performance to prove the sample works. The developed system provides a new set of considerations to take note when using thermal processes in creating microfluidic chips for thermoplastic polymers.